The Effect Of Letter Card Media On Early Literacy Abilities Of 5-6 Year Old Children - Ernawati, Ernawati; Muhtarom, Muhtarom; Fitri, Izza (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
This study aims to determine the effect of letter card media on the early literacy skills of children aged 5-6 years at RA Perwanida 4 Palembang. This type of research is quantitative with the Pre-Experimental Design experiment research method. This research design uses One Group Pretest - Posttest Design. The population of this study were group B children totaling 10 children and sampling using purposive sampling to obtain samples that represented the objectives of the research conducted and had sample selection criteria at RA Perwanida 4 Palembang. Data collection techniques used observation, tests, and documentation. The data analysis technique in this study used validity test, reliability test, normality test, homogeneity test, and t hypothesis test. Based on the results of the research that has been carried out, there is a significant influence on the early literacy skills of children aged 5-6 years on early literacy indicators in mentioning known letter symbols, recognizing the initial letter sounds of the names of objects around, understanding between the sound and shape of letters, mentioning groups of images that have the same sound or initial letter, writing their own names, and reading their own names. In addition, it is shown by 0.000, according to the results of hypothesis testing conducted using the SPSS program with a sequential sample test. Therefore, the significant value is not greater than 0.05. The data above shows that Ha is accepted and H0 is rejected. which means that there is a significant effect of letter card media on the early literacy skills of children aged 5-6 years at RA Perwanida 4 Palembang.